Habilidades sociais e adaptação da criança à pré-escola: concepções e habilidades sociais de educadores - Alho, Naara de Oliveira Gonçalves (2020)
School enrollment is a crucial moment in child development. The adaptation process in this space has been the object of theorization and research. School adaptation at this stage was understood from Bronfenbrenner’s concept of ecological transition, as a process of acquiring new social roles and affective bonds, established in order to provide mutual trust, favoring and influencing development, in addition to experiences that allow the formation and maintenance of psychic, cognitive and social skills. An important resource in adaptation is the child’s social skills repertoire to make friends, demonstrate empathy, self-control, emotional expressiveness, civility, assertiveness, solving interpersonal problems. In Brazilian literature, there are still few studies that have investigated the child’s adaptation period to school, particularly regarding the influence of social skills on the child’s insertion in school. The objectives of this study were to characterize the repertoire of social skills of children in pre-school age, to establish the relationship with indicators of adaptation to school, as well as to identify favorable and unfavorable indicators for school adaptation with an emphasis on teacher’s educational conceptions and social skills. Three schools were selected, two public ando one private, 4 teachers from these institutions and 10 children aged between 4 and 4 years and 6 months. For data collection, a Protocol for Observation of School Adaptation (PROAE) was prepared, which was completed by the teachers during the child’s first 4 weeks at school and in the first 3 months. The teachers and guardians of the children responded to the Scale of Social Behaviors of Preschoolers (PKBS-BR). Teachers and parents also answered a questionnaire with questions about how they conceived school adaptation and the Inventory of Social Educational Skills (IHSE-Prof). The data were computed in scores, organized in SPSS 25.0 spreadsheets and analyzed using descriptive and inferential statistics. The results indicated that children who had problems with school adaptation over 4 weeks and in the general evaluation of 3 months had worse repertoire of social skills and their teachers had a deficit or a lower average in terms of educational social skills, this data corroborates with some studies in the literature that have shown that children with a worse repertoire of social skills, have more problems for psychosocial adjustment. The responses of teachers and parents about school adaptation differed in some aspects, such as, for example, regarding the concept of school adaptation, parents associated adaptation as something geared to the child’s ability to adjust to the new environment, to behave well and demonstrate emotional well-being, while the teachers included their own performances and abilities to deal with this period. Some methodological and educational implications of the results were discussed, suggesting intervention planning based on them.